General Equilibrium Effects of Unemployment Compensation with Labor Force Participation - Sattinger, Michael (Journal of Labor Economics, 1995)
This article examines the effects of unemployment compensation when the size of the labor force depends on unemployment benefits. The analysis is based on an aggregate model with search and matching in which unemployment compensation affects the wage determination process and the number of jobs and workers. As with partial equilibrium models, unemployment compensation raises the unemployment rate and the ratio of unemployed to vacancies. However, wages may go up or down and firms may be better off. Generally, employed workers are worse off. Unemployment compensation transfers income from employed factors to unemployed factors, leading to greater input levels.